Biochemical effect of curcumin on hyperlipidemia induced in rats - Omayma A.R.,; Ragab A.; Abdel-Majeed A.D; Hassanin K.M.; Abdelghaffar M.M. (Medicamentul Veterinar)
This study was performed to investigate the effect of oral supplementation of curcumin, garlic extract and olive oil on lipid profile, nitric oxide, adiponectin, endothelin-1, blood glucose and some inflammatory markers in normal, diabetic and hyperlipidemic rats supplementing high fat and cholesterol-enriched diet. Forty female adult albino rats were divided into four equal groups of 10 rats each. Group (1): negative control received normal diet only, group (2): rats fed on normal diet and received curcumin orally, group (3): positive control received hyperlipidemic diet, group (4): rats fed on hyperlipidemic diet and received curcumin (350 mg/ 1 kg b.w.) orally. The obtained results revealed that, curcumin supplementations to hyperlipidemic rats showed a significant increase in serum HDL-cholesterol, nitric oxide, adiponectin and Endothelin-1 concentrations and significantly decrease in serum total cholesterol, triacylglycerols, LDL cholesterol, Fasting blood glucose, Glycated Hemoglobin (HbA1C), high sensitive C-reactive protein and Interleukin-6 levels. These results suggest that, curcumin supplementations may have some benefits in patients suffering from dyslipidemia and diabetes.